2017
DOI: 10.7770/safer-v5n2-art1211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia De Conductas Estereotipadas Y No Deseadas en El Caballo Fino Chilote en La Región De La Arucania, Chile.

Abstract: RESUMENEl objetivo del presente trabajo fue determinar la prevalencia de conductas estereotipadas y conductas no deseadas en el caballo chilote destinado a hipoterapia en dos centros terapéuticos; CRICAR, escuela de Hipoterapia y Equitación de Carabineros, en el Fundo El Entierro y Fundo Copin; todos ubicados en la novena región de la Araucanía, logrando observar 33 equinos de distinto sexo y edades. Estos fueron analizados en sus distintos hábitats según su rutina de entrenamiento, trabajo y potrero. Las cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…Studies of these breeds found stereotypies observed in 4-11% of Chilean Creole Horses [ 10 , 18 ] and 6-12% of English Thoroughbred horses [ 19 , 31 , 32 ]. Nonetheless, the frequency of abnormal behaviors found here was lower than reported previously in Colombia, Costa Rica, and Chile, where authors found 65%, 48.4%, and 56.9% of horses exhibiting these behaviors, respectively [ 26 , 33 , 34 ].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Studies of these breeds found stereotypies observed in 4-11% of Chilean Creole Horses [ 10 , 18 ] and 6-12% of English Thoroughbred horses [ 19 , 31 , 32 ]. Nonetheless, the frequency of abnormal behaviors found here was lower than reported previously in Colombia, Costa Rica, and Chile, where authors found 65%, 48.4%, and 56.9% of horses exhibiting these behaviors, respectively [ 26 , 33 , 34 ].…”
Section: Discussioncontrasting
confidence: 88%
“…In English Thoroughbred horses, the stereotypy most frequently seen was wind-sucking, followed by stall circling and weaving [ 31 , 32 ]. In Fino Chilote, the most frequent stereotype observed was weaving, followed by wind-sucking [ 34 ].…”
Section: Discussionmentioning
confidence: 99%